Postoperative Changes in Cerebral Metabolites Associated with Cognitive Improvement and Impairment after Carotid Endarterectomy: A 3T Proton MR Spectroscopy Study - Saito, H. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Cognitive function can improve or decline after carotid endarterectomy. Proton MR spectroscopy can be used evaluate cerebral metabolites, such as N-acetylaspartate, choline, and creatine, in vivo. The purpose of the present study was to determine whether postoperative changes in cerebral metabolites measured by using 3T proton MR spectroscopy were associated with changes in cognitive function after CEA. MATERIALS AND METHODS: In 100 patients undergoing CEA for ipsilateral cervical internal carotid artery stenosis (≥70%), brain proton MR spectroscopy was performed before and after surgery. NAA/Cr and Cho/Cr ratios were measured in regions of interest placed in the centrum semiovale of both cerebral hemispheres. Neuropsychological testing was also performed preoperatively and 1 month postoperatively. Multivariate statistical analysis of factors related to postoperatively changed cognition was performed, and odds ratios with 95% confidence intervals were calculated. RESULTS: On the basis of the neuropsychological assessments, 10 (10%), 80 (80%), and 10 (10%) patients were defined as having postoperatively improved, unchanged, and impaired cognition, respectively. A positive and high ΔNAA/Cr ratio (postoperative value–preoperative value) in the cerebral hemisphere ipsilateral to the operative site was significantly associated with postoperatively improved cognition (95% CI, 13.3–21.3; P = .0016). Negative and high absolute values of the ΔNAA/Cr ratio (95% CI, 0.018–0.101; P = .0039) and ΔCho/Cr ratio (95% CI, 0.042–0.135; P = .0046) in the ipsilateral cerebral hemisphere were significantly associated with postoperatively impaired cognition. CONCLUSIONS: Postoperative changes in cerebral metabolites measured by using proton MR spectroscopy were associated with changes in cognitive function after CEA.